Leadership in Action : In Focus - Organizational Changes-A Tale of Three Countries - Yi, Zhang (Center for Creative Leadership, 2008)
A comparison of studies by CCL and others on organizational changes and how they can be leveraged to accelerate leadership development-conducted in the United States, India, and more recently, China-offers new insights into how the lessons leaders learn through organizational changes vary among the respective countries.